Hubungan Kebiasaan Merokok Dengan Kejadian Hipertensi Pada Karyawan Pabrik Gula Tasikmadu - Larosa, Rega, dr. Nur Hidayat, Sp. PD, dr. Erika Diana Risanti (2015)
Background: Hypertension is a condition where there is an increase in blood pressure and usually someone did not realize if they are having hypertension. In Karanganyar Regency the prevalence of hypertension is 40,7%. Smoking is one of the that increase the risk of hypertension and affect the pathophysiology of hypertension. Purpose: To find out the relationship between smoking and the case of hypertension found among the employe of Tasikmadu Karanganyar sugar cane factory.. Method: This research used analitic observational method with cross sectional approach. To find out that both variables have the same meaning. Result:Out of 43 respondents that has the habit of smoking 32 are suffered with hypertension while the other 11 respondents don't have hypertension. Meanwhile from 43 respondents who doesn't smoke, 12 were found suffers hypertension and the other 31 don't have hypertension. After statistical analysis test being conducted with congtingensy coefficient corelation test the numer p = <0,05 obtained which means that there is a correlation with the meaning of r= +0,452 which means that someone who smoke could increase the risk of hypertension. Conclusion:There are meaningful relation between the habbits of smoking with hypertension in the employes of Tasikmadu Sugar Cane Factory